PEMETAAN REPOSITORI JURNAL DI INDONESIA DALAM KAITAN KORIDOR PERENCANAAN PEMBANGUNAN NASIONAL INDONESIA - Irhamni Ali; Aristianto Hakim (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2019)
Indonesia through National Medium Term Development Plan 2014-2019 (RPJMN 2014-2019) has established a Strategic Area Development Policy throughaccelerating the development of regional economic growth center by maximizing agglomeration benefit, exploring regional potentials and improving infrastructure provision efficiency in each region. It is therefore necessary to improve exibility to information to increase the economy and the region. The development of repository as part of information technology development allow access to information to disseminate information in generating any development planning policy. This study discussed if researches done by regional universities, through journal repositories produced, meet the goverment policy. The samples in the study are 1,355 journal repositories spread in 5 areas of Java-Bali, Sumatra, kalimantan, Sulawesi, Nusa Tenggara-Maluku and Papua. As the processing data, the study apllied data mining approach. It was obtained that the current journal repositories are still dominated by Java-Bali, Sumatra, Sulawesi, kalimantan, Nusa Tenggara-Maluku-Papua. Accordingly, it can be concluded that research conducted in the regions in Indonesia have not met the RP JMN 2014-2019.